Magnetic nano composite material with adjustable and controllable magnetic performance and preparation method of magnetic nano composite material
By combining cell microvesicles with iron oxide nanoparticles, electroporation technology is used to build magnetic nanocomposites with different magnetic response speeds, solving the problem of magnetic performance regulation in the existing technology, and achieving effective biosafety and magnetic performance Regulation, suitable for a variety of application fields.
Patent Information
- Application Number
- CN202411347445.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-26
- Publication Date
- 2024-12-31
- Estimated Expiration
- 2044-09-26
AI Technical Summary
The existing magnetic performance control methods of magnetic nanocomposites have problems such as high interference, uncontrollable microsphere size, insufficient biosafety and environmental protection, especially in biomedical applications, which are difficult to effectively regulate magnetic performance.
Cell microvesicles are combined with iron oxide nanoparticles, loaded into the vesicles through electroporation technology, and used voltage to construct magnetic nanocomposites with different magnetic response speeds, combining iron oleate complexing and citric acid coating steps to prepare Magnetic nanocomposite material with spherical structure.
It has achieved good biosafety and magnetic properties of magnetic nanocomposites, and is suitable for catalysis, magnetic heat transfer, magnetic storage, biomedicine and other fields, especially in the wide application of biomedical field, showing excellent performance.
Smart Images

Figure CN119215873A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of nano material science and technology, and specifically relates to a magnetic nano composite material with adjustable magnetic properties and a preparation method thereof. Background Art
[0002] Magnetic nanocomposites are multi-component materials, usually made by combining nanoscale magnetic materials with polymers, silica, carbon or metal organic framework materials, and are widely used in magnetic separation, catalysis, medical diagnosis, treatment, etc. Magnetic nanocomposites exhibit the characteristics of responding to external magnetic fields and show special properties when exposed to static or alternating magnetic fields, and can be used for brakes, magnetic separation or drug delivery.
[0003] The polymer coating method usually grinds ferromagnetic metal materials, such as cobalt powder or iron powder, into ferromagnetic materials of nanometer to micrometer size, and then coats the polymer on the surface of the magnetic material through solvent evaporation technology to form a magnetic nanocomposite. In this process, parameters such as stirring speed and polymer viscosity will directly affect the size and shape of the composite material, and the magnetization intensity will also decrease with the increase of coating thickness. The magnetic properties of the magnetic nanocomposite can be controlled by changing the grinding time of the magnetic material and the stirring time of the material and the polymer. This method has great interference, the size of the prepared microspheres is uncontrollable, and it is impossible to effectively control the magnetic properties of the magnetic nanocomposite.
[0004] In addition, some researchers have proposed to construct magnetic nanocomposites with different magnetic response speeds by changing the feed ratio. For example, after micron-sized polystyrene particles are swollen in an aqueous solution of N-methyl-2-pyrrolidone (NMP), they are mixed with superparamagnetic iron oxide nanoparticles, and the magnetic nanoparticles can diffuse into the polymer microspheres. The magnetic properties of magnetic polymer microspheres can be changed by regulating the swelling ratio of the polymer and the concentration of the magnetic nanoparticles. However, as the swelling rate of the polymer solution increases, polymer loss will occur. In addition, since NMP has acute toxicity and cannot be discharged at will, the environmental protection and biosafety of the synthesis process need to be examined, which affects its scope of application.
[0005] The bionic technology developed in recent years can combine cell membranes with functional nanoparticles, and has played a huge role in biomedical research. At present, some researchers use cell membranes to coat magnetic nanoparticles. They collect cell membranes from different sources such as cancer cells, immune cells, red blood cells, and bacteria through a top-down approach and coat the cell membranes on the surface of magnetic nanoparticles through ultrasound or co-extrusion to construct a magnetic nanocomposite with a natural membrane structure. This method cannot directly regulate the magnetic properties of magnetic nanocomposites, but the idea of using biological natural components to construct magnetic nanocomposites with good biosafety is worth learning from. Based on this, we hope to design a magnetic nanocomposite with adjustable magnetic properties that has good biosafety and can regulate magnetism. Summary of the invention
[0006] In view of the problems and shortcomings of the prior art, the present invention provides a method for preparing a magnetic nanocomposite material with adjustable magnetic properties, comprising the following steps:
[0007] S1: dissolving FeCl3·6H2O and sodium oleate in a solvent, placing the mixture in a container, introducing nitrogen, heating the mixture in an oil bath, reacting and stirring the mixture to obtain a reactant, washing the reactant with rotary evaporation, and vacuum drying the mixture to obtain an iron oleate complex precursor;
[0008] S2: dissolving the iron oleate complex precursor obtained in S1 and oleic acid in n-octyl ether, then placing in a container, introducing nitrogen gas to heat, then cooling, precipitating nanoparticles, and washing through a filter element to obtain oleic acid-coated iron oxide nanoparticles;
[0009] S3: dispersing the oleic acid-coated iron oxide nanoparticles obtained in S2 in a mixture of 1,2-dichlorobenzene and DMF, adding anhydrous citric acid, introducing nitrogen gas, heating and stirring to react, precipitating the nanoparticles, and obtaining the citric acid-coated iron oxide nanoparticles by magnetic adsorption;
[0010] S4: Cultivate mouse fibroblasts, collect cell microvesicles by centrifugation, mix the cell microvesicles and citric acid-coated iron oxide nanoparticles in a volume ratio of 1:1, add them to an electroporation dish, perform electroporation, and obtain a magnetic nanocomposite material.
[0011] Furthermore, the nitrogen gas is introduced for 15-20 minutes in S1 to remove excess air in the reaction vessel, and the reaction is continued for 3.5-4 hours after the temperature is raised to 70°C.
[0012] Furthermore, the mass ratio of FeCl3·6H2O to sodium oleate described in S1 is 3.6:12.17.
[0013] Furthermore, the drying time described in S1 is 10-12 hours.
[0014] Furthermore, the heating temperature described in S2 is 290° C., the centrifugal speed is 12000 rpm, and the centrifugal time is 5 min.
[0015] Furthermore, the mass ratio of the iron oleate complex precursor to oleic acid described in S2 is 1.57:1.
[0016] Furthermore, the mass ratio of oleic acid to anhydrous citric acid in S3 is 1:2, and the stirring time is 24 hours.
[0017] Furthermore, the centrifugation time described in S4 is 2 hours, and the voltage during the electroporation process is 100V, 250V, and 500V.
[0018] A magnetic nanocomposite material with adjustable magnetic properties. The nanocomposite material is a spherical structure with magnetic nanomaterials loaded inside.
[0019] Beneficial Effects
[0020] (1) The preparation method of a magnetic nanocomposite material with adjustable magnetic properties provided by the present invention adopts iron oxide nanoparticles with good biosafety, chemical catalytic properties, magnetism and low price, and cell microvesicles are phospholipid bilayer membrane vesicles that can be secreted by various types of cells. As an important medium for intercellular communication, they can be found in biological fluids such as cell culture medium, blood, saliva, urine and breast milk. According to their size and production mechanism, they are usually divided into three different groups: cell microvesicles, apoptotic bodies and exosomes. Cell microvesicles are directly germinated from cell membranes and have a particle size of 100-1000 nanometers. Cell microvesicles carry biological information such as proteins, nucleic acids and lipids related to their mother cells. More importantly, they have the characteristic of having a natural cavity structure, which provides a huge advantage for the construction of magnetic nanocomposites.
[0021] (2) The magnetic nanocomposite material with adjustable magnetic properties provided by the present invention is based on the natural cavity structure of cell microvesicles and the excellent magnetic properties of iron oxide nanoparticles. The iron oxide nanoparticles are loaded into the vesicles by electroporation technology, and magnetic nanocomposites with different magnetic response speeds are constructed by changing the voltage. The magnetic nanocomposites are applied in the fields of catalysis, magnetic heat transfer, magnetic storage, batteries, biomedicine, etc. In particular, in the field of biomedicine, the magnetic separation, imaging contrast agent, magnetic hyperthermia, magnetic targeting, biological antibacterial and immunotherapy have been widely used. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] In order to more clearly illustrate the technical solutions of the exemplary embodiments of the present invention, the following is a brief introduction to the drawings required for use in the embodiments. It should be understood that the following drawings only illustrate certain embodiments of the present invention and should not be regarded as limiting the scope. For those of ordinary skill in the art, other relevant drawings can be obtained based on these drawings without creative work. In the drawings:
[0023] Figure 1 This is a diagram of hydrophilic and hydrophobic magnetic nanoparticles according to Example 1 of the present invention;
[0024] Figure 2 This is a diagram showing the magnetic adsorption effect of a magnetic nanocomposite material constructed with different electrotransfer parameters according to Example 1 of the present invention;
[0025] Figure 3 This is a transmission electron microscope image of the magnetic nanocomposite material of Example 1 of the present invention. DETAILED DESCRIPTION
[0026] The following will be combined with Example 1 of the present invention and the attached Figures 1 to 3 , clearly and completely describe the technical solution of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0027] Example 1
[0028] S1: First, 3.6g of FeCl3·6H2O and 12.17g of sodium oleate were dissolved in 27mL of ethanol, 20mL of deionized water, and 46.7mL of n-hexane to obtain a mixed solution. The mixed solution was then placed in a three-necked flask and nitrogen was introduced into it for 20 minutes. The three-necked flask was then placed in an oil bath, heated to 70°C at room temperature, and stirred and refluxed at this temperature for 4 hours. After the reaction was completed, the reactants were transferred to a separatory funnel, and the organic layer containing the oleic acid iron complex in the reactants was washed several times with 50mL of deionized water. After washing, the residual n-hexane was further removed using a rotary evaporator, and the mixture was placed in a vacuum drying oven for 10 hours to obtain an oleic acid iron complex precursor in the form of an oily waxy solid;
[0029] S2: Weigh 0.45 g of the iron oleate complex precursor obtained in S1 and 0.286 g of oleic acid and dissolve them in 12.346 mL of n-octyl ether to obtain a reactant, place it in a three-necked flask, introduce nitrogen into the flask to remove excess air in the device, and then heat it to 290°C at a constant heating rate and maintain it at this temperature for 30 minutes. After the reaction is completed, place the three-necked flask containing the nanocrystal reactant in ice water and cool it to room temperature, then add 50 mL of ethanol to precipitate the nanoparticles, and wash them by centrifugation for multiple times at a centrifugal rate of 12000 rpm and a centrifugal time of 5 minutes to obtain oleic acid-coated iron oxide nanoparticles;
[0030] S3: 50 mg of oleic acid-coated iron oxide nanoparticles were dispersed in 15 mL of a mixture of 1,2-dichlorobenzene and DMF (1:1, V / V), placed in a three-necked flask, and 100 mg of anhydrous citric acid was added. Nitrogen was introduced into the device to remove oxygen, the temperature was raised to 100°C at room temperature, and refluxed and stirred for 24 h. After the reaction was completed, ether was added to the three-necked flask to precipitate the nanoparticles, and the citric acid-coated iron oxide nanoparticles that were collected and precipitated were collected by magnetic adsorption, and allowed to stand in a fume hood for a period of time to remove excess ether. The dried iron oxide nanoparticles were weighed and a certain amount of deionized water was added to obtain a citric acid-coated iron oxide nanoparticle solution with a fixed concentration and good dispersibility in water, which was sealed and stored in a refrigerator at 4°C to obtain citric acid-coated iron oxide nanoparticles (NPs).
[0031] S4: Culture mouse fibroblasts (L929) in an incubator at 37°C, containing 5% CO2 and 95% air; when the cells can almost cover the entire culture bottle, they can be cultured with serum-free DMEM high-glucose medium for 24 hours to stimulate the cells to secrete extracellular vesicles by starvation culture; collect the culture supernatant and remove excess cell debris by pre-centrifugation (centrifugation rate is 2000rpm, centrifugation rate is 10min); the supernatant after centrifugation is centrifuged at 4°C, 5000g ultrahigh speed centrifuge for 2 hours to collect and concentrate extracellular vesicles, and the collected microvesicles are resuspended in a small amount of PBS, and the protein content is determined by BCA protein assay. The vesicles collected from every 200mL culture supernatant are resuspended in 4mL PBS, and the protein content is about 2.47mg / mL; store in a -80°C refrigerator for use to obtain cell microvesicles (MVs);
[0032] 2.47 mg / mL, 500 μL of MVs and 10 mg / mL, 500 μL of NPs were mixed evenly, added to an electroporation dish, and electroporation experiments were carried out under the conditions of 100 V and 350 μF; magnetic nanocomposites were prepared under the conditions of 250 V and 500 V in the same way; after electroporation, they were placed in centrifuge tubes and incubated at 37°C for 30 minutes to restore the membrane structure of the vesicles; then MVs@NPs prepared under different voltages (100 V, 250 V, 500 V) were collected by magnetic separation; they were stored in a 4°C refrigerator for future use, and magnetic nanocomposites with adjustable magnetic properties were obtained.
[0033] Combination Figure 1 It can be seen that the aqueous iron oxide nanoparticles coated by citric acid are uniformly dispersed in water, and the oily iron oxide nanoparticles coated by oleic acid are insoluble in water and only soluble in chloroform. The prepared iron oxide nanoparticles need to have good dispersibility in water. The final material synthesized by the three-step method, the iron oxide nanoparticles coated with citric acid, uses the ligand exchange method to make it uniformly dispersed in water without obvious precipitation.
[0034] Combination Figure 2 It can be seen that after the same magnetic adsorption time of 15 minutes, the magnetic adsorption amount of the magnetic nanocomposites constructed by different electroconversion voltages is significantly different. The reason is that in the constructed magnetic nanocomposites, the loading amount of magnetic nanomaterials inside the vesicles is different. Figure 3 It can be seen from the transmission image of the magnetic nanocomposite material that the small image in the upper right corner corresponds to the (311) crystal plane of γ-Fe2O3.
[0035] The magnetic nanoparticles NPs and the prepared magnetic nanocomposite MVs@NPs were dispersed in pure water, transferred to a glass tube, and nitric acid was used to nitric acid. The iron content was determined by atomic absorption spectrometry, and the encapsulation efficiency was calculated by the following formula, as shown in Table 1.
[0036]
[0037]
[0038] Table 1 Encapsulation efficiency of NPs and MVs@NPs at different electroporation voltages
[0039] The present invention provides a method for preparing a magnetic nanocomposite material with adjustable magnetic properties. Cell microvesicles with a natural cavity structure are used in combination with iron oxide nanoparticles to obtain excellent magnetic properties. The iron oxide nanoparticles are then loaded into the vesicles using electroporation technology. A magnetic nanocomposite material with different magnetic response speeds is constructed by changing the voltage. The method is easy to operate, does not require large equipment during the process, and does not require high professionalism of the operator. The prepared magnetic nanocomposite material has good biosafety and good application prospects.
[0040] The present invention provides a magnetic nanocomposite material with adjustable magnetic properties, which is spherical under a transmission electron microscope and loaded with magnetic nanomaterials. The synthesized magnetic nanoparticles have small particle sizes and good dispersibility in water, so single nanoparticles cannot be manipulated by a magnet. After being transferred into vesicles, the particles aggregate, and the synthesized magnetic nanocomposite material can be manipulated by a magnet.
Claims
1. A method for preparing a magnetic nanocomposite material with adjustable magnetic properties, characterized in that: The following steps are involved: S1: dissolving FeCl3·6H2O and sodium oleate in a solvent, placing the mixture in a container, introducing nitrogen, heating the mixture in an oil bath, reacting and stirring the mixture to obtain a reactant, washing the reactant with rotary evaporation, and vacuum drying the mixture to obtain an iron oleate complex precursor; S2: dissolving the iron oleate complex precursor obtained in S1 and oleic acid in n-octyl ether, then placing in a container, introducing nitrogen gas to heat, then cooling, precipitating nanoparticles, and washing through a filter element to obtain oleic acid-coated iron oxide nanoparticles; S3: dispersing the oleic acid-coated iron oxide nanoparticles obtained in S2 in a mixture of 1,2-dichlorobenzene and DMF, adding anhydrous citric acid, introducing nitrogen gas, heating and stirring to react, precipitating the nanoparticles, and obtaining the citric acid-coated iron oxide nanoparticles by magnetic adsorption; S4: Cultivate mouse fibroblasts, collect cell microvesicles by centrifugation, mix the cell microvesicles and citric acid-coated iron oxide nanoparticles in a volume ratio of 1:1, add them to an electroporation dish, perform electroporation, and obtain a magnetic nanocomposite material.
2. The method for preparing a magnetic nanocomposite material with controllable magnetic properties according to claim 1, characterized in that: The nitrogen gas is introduced for 15-20 minutes in S1 to remove excess air in the reaction vessel, and the reaction is continued for 3.5-4 hours after the temperature is raised to 70°C.
3. The method for preparing a magnetic nanocomposite material with controllable magnetic properties according to claim 1, characterized in that: The mass ratio of FeCl3·6H2O to sodium oleate described in S1 is 3.6:12.
17.
4. The method for preparing a magnetic nanocomposite material with controllable magnetic properties according to claim 1, characterized in that: The drying time described in S1 is 10-12 hours.
5. The method for preparing a magnetic nanocomposite material with controllable magnetic properties according to claim 1, characterized in that: The heating temperature described in S2 is 290° C., the centrifugal speed is 12000 rpm, and the centrifugal time is 5 min.
6. The method for preparing a magnetic nanocomposite material with controllable magnetic properties according to claim 1, characterized in that: The mass ratio of the iron oleate complex precursor to oleic acid described in S2 is 1.57:
1.
7. The method for preparing a magnetic nanocomposite material with controllable magnetic properties according to claim 1, characterized in that: The mass ratio of oleic acid to anhydrous citric acid in S3 is 1:2, and the stirring time is 24 hours.
8. The method for preparing a magnetic nanocomposite material with controllable magnetic properties according to claim 1, characterized in that: The centrifugation time described in S4 is 2 h, and the voltage during the electroporation process is 100 V, 250 V, and 500 V.
9. A magnetic nanocomposite material with adjustable magnetic properties obtained by the preparation method according to any one of claims 1 to 8, characterized in that: The magnetic nano-composite material is a spherical structure, and the magnetic nano-material is loaded inside.
Citation Information
Patent Citations
Microvesicles derived from nucleated, mammalian cells and use thereof
CN102596177A
Tumor-targeted delivery carrier based on cell-derived micro-vacuoles, preparation method and application
CN106692984A
Method for loading loaded objects through macromolecule vesicle electroporation process
CN107281105A
Preparation method of exosome capable of simultaneously loading chemical drug and nano-material
CN108114290A
Preparation method of ferroferric oxide nanoparticles wrapped by cancer cell membranes
CN112402630A